Corn seed treatment with naphthalic anhydride against isoxaflutole phytotoxication action - de Goes Maciel, Cleber Daniel; Velini, Edivaldo Domingues [UNESP]; Martins, Dagoberto [UNESP]; Negrisoli, Eduardo [UNESP]; Tofolli, Gustavo Radomille [UNESP] (Wfl Publ, 2012)
Weed control in corn crop requests efficient techniques and among them, the safeners are considered an important tool by increasing herbicides selectivity levels and safety. With the objective of increasing the selectivity of isoxaflutole herbicide in corn crop, an experiment was conducted under field conditions, by using seed treatment with naphthalic anhydride safener. Randomized complete blocks experimental design was used with six replications. The treatments were disposed in a factorial scheme 2x2x2, constituted by seeds treatment or not, of Cargill 435 (isoxaflutole tolerant) and Colorado 32 (isoxaflutole sensitive) corn hybrids with naphthalic anhydride (NA) (5.0 g kg(-1)), being both genotypes submitted or not to the application of isoxaflutole herbicide (60 g e.a ha(-1)) in pre-emergency condition. The association of seed treatment with naphthalic anhydride to isoxaflutole herbicide reduced significantly the leaves bleaching of corn hybrids, starting from 14 days after application, and also provided higher mean weight of corn ears, mean diameter of corn ear and number of grains for row. In the absence of isoxaflutole, the use of NA seed treatment increased Cargill 435 and Colorado 32 hybrids yield 7.2%. In the presence of isoxaflutole, by using NA seed treatment yield of corn hybrids increased 16.9% and 7.0%, respectively, for Cargill 435 and Colorado 32 hybrids.
Keywords: Herbicide; phytotoxicity; safener; carotenes